2012
DOI: 10.1101/cshperspect.a011338
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Quality Control Mediated by PINK1 and Parkin: Links to Parkinsonism

Abstract: Mutations in Parkin or PINK1 are the most common cause of recessive familial parkinsonism. Recent studies suggest that PINK1 and Parkin form a mitochondria quality control pathway that identifies dysfunctional mitochondria, isolates them from the mitochondrial network, and promotes their degradation by autophagy. In this pathway the mitochondrial kinase PINK1 senses mitochondrial fidelity and recruits Parkin selectively to mitochondria that lose membrane potential. Parkin, an E3 ligase, subsequently ubiquitina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
261
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(269 citation statements)
references
References 95 publications
(161 reference statements)
6
261
0
2
Order By: Relevance
“…This points to an increased elimination of mitochondria through lysosomal degradation in Pat#1 and Pat#2. This was also confirmed by the enhanced translocation of Parkin to mitochondria 33,34 in Pat#1 cells compared with the control cells (Supplementary Figure S2a).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…This points to an increased elimination of mitochondria through lysosomal degradation in Pat#1 and Pat#2. This was also confirmed by the enhanced translocation of Parkin to mitochondria 33,34 in Pat#1 cells compared with the control cells (Supplementary Figure S2a).…”
Section: Resultssupporting
confidence: 63%
“…Despite no differences could be detected in the overall level of mitochondrial proteins in both resting conditions and after nutrient deprivation (Supplementary Figure S2b), MCU (in the inner mitochondrial membrane) and Tom20 (in the outer mitochondrial membrane (OMM)) show a much faster degradation in Pat#1 compared with control fibroblasts after blocking protein synthesis with cycloheximide, indicating a higher organelle turnover (Figure 2c). 33,34 Defective mitochondrial Ca 2+ homeostasis in 13514A4G fibroblasts. As previously reported, an impairment of mitochondrial Ca 2+ handling is associated with mitochondrial diseases.…”
Section: Resultsmentioning
confidence: 99%
“…The most thoroughly characterized pathway for mitochondrial priming is that of PINK1- PRKN/PARK2 signaling [40,52]. Upon mitochondrial depolarization, PINK1 accumulates on the outer mitochondrial membrane (OMM) to recruit the cytosolic E3 ubiquitin ligase PRKN/PARK2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PINK1 phosphorylates Parkin on serine 65 of its ubiquitin-like (Ubl) domain, leading to an increase of its ubiquitination activity [6]. However, PINK1 must play an additional role in Parkin activation since the non-phosphorylatable S65A mutant of Parkin is still able to translocate to mitochondria (albeit more slowly), whereas PINK1 deletion or mutation completely abolishes translocation [1]. Moreover, the phosphomimetic S65E mutant of Parkin still requires PINK1 for translocation to mitochondria.…”
mentioning
confidence: 99%
“…Since then, functional links between the two proteins have been piling up. In Drosophila, mitochondrial dysfunction caused by Parkin or PINK1 mutants can be rescued by Parkin overexpression, suggesting that PINK1 acts upstream of Parkin (reviewed in [1]). The PINK1 protein is a serine/threonine kinase that accumulates and becomes active on mitochondria in response to their depolarization, e.g., after CCCP (carbonyl cyanide m-chlorophenyl hydrazone) treatment.…”
mentioning
confidence: 99%